2016
DOI: 10.1002/ecs2.1225
|View full text |Cite
|
Sign up to set email alerts
|

Testing epidemiological functional groups as predictors of avian haemosporidia patterns in southern Africa

Abstract: Abstract. Understanding the dynamics of multihost parasites and the roles of different host species in parasite epidemiology requires consideration of the whole animal community. Host communities may be composed of hundreds of interacting species, making it necessary to simplify the problem. One approach to summarizing the host community in a way that is relevant to the epidemiology of the parasite is to group host species into epidemiological functional groups (EpiFGs). We used EpiFGs to test our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
1
6
0
1
Order By: Relevance
“…prevalence (Ellis et al 2016), but this study may be among the first reports of a similar effect for Leucocytozoon spp., although the effect was less prominent. The minimal effect of host abundance on Haemoproteus infections was in concurrence with other studies, which note that Haemoproteus infections are more driven by host choice (Clark and Clegg, 2017), and subsequently more susceptible to host ecology factors such as roosting and foraging behaviour (Lutz et al 2015; Hellard et al 2016). Similarly, the strong influence of season on Haemoproteus prevalence is consistent with the seasonal nature of several aspects of host behaviour and ecology, with many activities taking place during summer months (Hockey et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…prevalence (Ellis et al 2016), but this study may be among the first reports of a similar effect for Leucocytozoon spp., although the effect was less prominent. The minimal effect of host abundance on Haemoproteus infections was in concurrence with other studies, which note that Haemoproteus infections are more driven by host choice (Clark and Clegg, 2017), and subsequently more susceptible to host ecology factors such as roosting and foraging behaviour (Lutz et al 2015; Hellard et al 2016). Similarly, the strong influence of season on Haemoproteus prevalence is consistent with the seasonal nature of several aspects of host behaviour and ecology, with many activities taking place during summer months (Hockey et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…exhibit a more host specialist approach (Bensch et al 2000); however, lineages within both genera still display great flexibility in host range (Ricklefs, 2004; Syzmanski and Lovette, 2005). Several studies have described Plasmodium and Haemoproteus infection patterns in the sub-Saharan region (Cumming et al 2013; Hellard et al 2016), but fewer contain additional information on Leucocytozoon infections (Schultz et al 2011; Lutz et al 2015). Although Haemoproteus and Leucocytozoon infections are generally less virulent than Plasmodium , and their host generality and vectors differ (Valkiūnas, 2005), their occurrences in the same locations and host communities (Okanga et al 2013 a ; Galen and Witt, 2014) allow us to draw inferences about the relative importance of host preference (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies have presented data on the prevalence and diversity of haemosporidian parasites in closely related bird species. Differences in prevalence between species are associated with several factors and the interactions between those, including life-history traits and ecology of the hosts and vectors, parasite characteristics and environmental conditions, that may affect the activity of vectors and the development of parasites (Sol et al 2000 ; Gupta et al 2011 ; Quillfeldt et al 2011 ; Hellard et al 2016 ; Chakarov et al 2020 ; Ciloglu et al 2020b ; Ellis et al 2020 ). Also different behavioural characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The love and cruelty also of various people including the chiefs and their subjects, dangers in everyday and in livelihood styles, are very well outlined. Hellard et al [1], on their study on avian malaria (Plasmodium and Haemoproteus), used 176 wetland associated birds species and 3414 that were captured at Lake Ngami. Robbins et al [17][18] later confirmed the rich biodiversity comprising terrestrial and wetland mammals, fish, reptiles, and birds, including domestic animals of kind, among others of the Ngami area using archeaological evidence.…”
Section: Historical/archival Records 1849-1966mentioning
confidence: 99%
“…Lake Ngami, a natural dead end water body without outflow [1], situated in the Kalahari Desert to the South of the famous inland Okavango River Delta [2] located in Ngamiland District of North western Botswana [3][4]. It receives most of its water as a result of tropical rainfall to the north in Angola that feeds the Okavango River, which overflows into the lake [5].…”
Section: Introductionmentioning
confidence: 99%